Challenges of Curtin-AVU-AAU Distance Learning Program in Ethiopia: A Case Study - Belwal, Rakesh; Dawit Ayalew Kassa; Medhanie Gaim Asgedom (MERLOT Journal of Online Learning and Teaching, 2010)
Distance education programs are emerging globally in the form of joint ventures among higher educational institutions. This paper describes the research undertaken to explore one such joint venture program in business between Australian and African universities. This study utilizes both primary and secondary data gathered through a review of the literature, consultations with program administrators, interviews with faculty members, direct observations, and questionnaires administered to sample students. This case study explores factors affecting the program. Using quantitative and qualitative analytical tools, this study discusses the outcomes of the analyses to facilitate experiential learning. It finds that for students originating mainly from remote regions of Ethiopia, distance learning can offer good opportunities of receiving cost-effective, quality-education on their doorsteps. This experience could contribute immensely to the extension of such programs to other regions of the country. Although the joint venture reveals the potential of coordinated educational efforts, internal weaknesses and inefficiencies need serious attention to ensure the success of such initiatives in the future.
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Ethiopia; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; F:learning; F:outcomes; P:technology; Q:distance learning; Q:higher education; R:case study; R:interview; R:observation; R:qualitative; R:quantitative; R:questionnaire; T:distance learning program; Z:Alliances; Z:Distance learning; Z:Education reform; Z:Market entry; Z:Qualitative research; Z:Technological change; __C:filed:1; publicImportV1; ⛔ No DOI found